IMPLEMENTASI TEKNOLOGI INFORMASI UNTUK PERAMALAN DINAMIKA BISNIS (STUDI PADA BISNIS VALAS) - Khofifah Amalia; Amalia Salsabila Ariyanto (J-MACC, 2020)
This study aims to determine the implementation of information technology in foreign exchange. By using quantitative and qualitative research methods as well as associative. research that comes from the presence of data and utilizes existing theories as an explanation. With the development of technology, every company tries to always provide the best service to its customers in the business field. In the business sector, technology plays an important role, especially in banking. It cannot be separated from one that we may rarely hear but which plays an important role in the business world, namely the existence of foreign exchange. Foreign currency or commonly referred to as foreign exchange is the currency that is used as a legal tender in the country. Foreign currency will have a value if that foreign currency can be exchanged for another foreign currency without restrictions. Foreign exchange transactions can occur in the foreign exchange market.